The Stress and Adversity Inventory for Adults (Adult STRAIN) in German: An overview and initial validation - Sturmbauer, Sarah C.; Shields, Grant S.; Hetzel, Eva-Luca; Rohleder, Nicolas; Slavich, George M. (PloS one, 2019)
Life stress is a key determinant of poor mental and physical health, but until recently no instrument existed for efficiently assessing cumulative stress exposure and severity across the entire lifespan. The Stress and Adversity Inventory (STRAIN) is an online, interview-based stress assessment system that was developed to address this need. We examined the concurrent, predictive, and discriminant validity of a German translation of the STRAIN by administering the instrument, along with several other measures of stress and health, to 298 adults (81 men, 217 women, Mage = 30.3 years). The German STRAIN demonstrated excellent concurrent validity, as evidenced by associations with other instruments assessing early adversity (|rs|≥.62, ps≤.001). It also correlated with instruments assessing recent life event exposure in adulthood (|rs|≥.48, ps≤.001), as well as recent perceived stress (|rs|≥ .25, ps≤.001) and recent chronic stress levels (|rs|≥ .19, ps≤.001). Additionally, the German STRAIN showed strong predictive validity in relation to anxiety symptoms (|rs|≥ .22, ps≤.001) and depressive symptoms (|rs|≥ .33, ps≤.001). Finally, the German STRAIN showed good discriminant validity, with lifetime stressor count being unrelated to personality features like neuroticism. These results demonstrate that the German version of the STRAIN is a valid tool for assessing lifetime stress exposure and severity. Additional research is needed to examine how the German STRAIN predicts psychological and biological stress reactivity and physical health outcomes.